Pupillary behavior in relation to wavelength and age - Lobato-Rincón, Luis-Lucio; Cabanillas-Campos, Maria del Carmen; Bonnin-Arias, Cristina; Chamorro-Gutiérrez, Eva; Murciano-Cespedosa, Antonio; Sánchez-Ramos Roda, Celia (Frontiers in Human Neuroscience, 2014)
Pupil light reflex can be used as a non-invasive ocular predictor of cephalic autonomic nervous system integrity. Spectral sensitivity of the pupil´s response to light has, for some time, been an interesting issue. It has generally, however, only been investigated with the use of white light and studies with monochromatic wavelengths are scarce. This study investigates the effects of wavelength and age within three parameters of the pupil light reflex (amplitude of response, latency, and velocity of constriction) in a large sample of younger and older adults (N=97), in mesopic conditions. Subjects were exposed to a single light stimulus at four different wavelengths: white (5600 ºK), blue (450 nm), green (510 nm) and red (600 nm). Data was analysed appropriately, and, when applicable, using the General Linear Model (GLM), Randomised Complete Block Design (RCBD), Student´s t test and/or ANCOVA. Across all subjects, pupillary response to light had the greatest amplitude and shortest latency in white and green light conditions. In regards to age, older subjects (46-78 years) showed an increased latency in white light and decreased velocity of constriction in green light compared to younger subjects (18-45 years old). This study provides data patterns on parameters of wavelength-dependent pupil reflexes to light in adults and it contributes to the large body of pupillometric research. It is hoped that this study will add to the overall evaluation of cephalic autonomic nervous system integrity.